Lipophosphoglycan From Dermotropic New World Leishmania Upregulates Interleukin-32 and Proinflammatory Cytokines Through TLR4 and NOD2 Receptors - Silveira, Murilo Barros; Gomes, Rodrigo Saar; Shio, Marina Tiemi; Rugani, Jeronimo Nunes; Paranaiba, Larissa Ferreira; Soares, Rodrigo Pedro; Ribeiro-Dias, Fátima (Frontiers in Cellular and Infection Microbiology, 2022)
Interleukin-32 (IL-32) is produced during Leishmania infection, but the components of the parasite that induce its production are unknown. An important multivirulence factor of Leishmania spp. protozoa is the lipophosphoglycan (LPG), which plays a crucial role in the host-parasite interaction. Here, the ability of LPGs from two dermotropic Leishmania species to induce IL-32 production was evaluated in human peripheral blood mononuclear cells (PBMCs). Additionally, the potential receptors involved in this activation were assessed. PBMCs from healthy individuals were stimulated with LPGs from L. amazonensis (La) or L. braziliensis (Lb), live promastigotes of La or Lb and E. coli lipopolysaccharide (LPS, TLR4 agonist) as control. Blockers of TLR4 (Bartonella quintana LPS or monoclonal antibody) and Ponatinib (RIPK2 inhibitor, NOD2 pathway) were used to evaluate the receptors. ELISA was performed for IL-32 expression and cytokine (IL-1β and IL-6) production in cell lysates and in supernatants, respectively. Expression of TLR4 (2 h, 24 h) was assessed by flow cytometry. IL-32 mRNA transcript was analyzed by qPCR. It was observed that LPG from Leishmania, like whole parasites, induced the production of IL-32, IL-1β and IL-6. Both LPGs induced the expression of IL32 mRNA. The production of IL-32 was earlier detected (6 h) and positively associated with the production of IL-1β and IL-6. The induction of cytokines (IL-32, IL-1β and IL-6) was dependent on TLR4 and NOD2. The TLR4 was internalized after interaction with LPG. Therefore, our data suggest that LPGs from La and Lb are components of Leishmania able to upregulate IL-32 and other pro-inflammatory cytokines in a TLR4- and NOD2-dependent manner. In addition, LPG-induced IL-32 seems to be necessary for IL-1 and IL-6 production. To identify the parasite factors and host receptors involved in IL-32 induction is crucial to reveal potential targets for novel strategies to control leishmaniasis.